THE MATERNAL MICROBIOME: IMPLICATIONS FOR FERTILITY, PREGNANCY, AND NEONATAL HEALTH - Niko Koridze; Tsotne Dadiani; Mariam Morchadze; Keti Kebadze; Melita Modebadze; Mariam Gigiadze; Sofiko Goshadze; Keti Azikuri; Nika Gorduladze; Nika Gorduladze; Mariam Beriashvili; Elene Vardosanidze; et al. (The Conference Hub, 2025)
The maternal microbiome, encompassing microbial communities of the gut, vaginal tract, oral cavity, and placenta, experts profound effects on reproductive health, pregnancy outcomes, and early neonatal development. Recent advances in high-throughput sequencing and metabolomic profiling have illuminated the dynamic nature of maternal microbial ecosystems, revealing their pivotal role in fertility, immune modulation, and the programming of offspring health. Dysbiosis of maternal microbiota has been implicated in adverse obstetric outcomes, including infertility, preterm birth, preeclampsia, gestational diabetes, mellitus (GDM), and altered neonatal immune responses. This review synthesizes current understanding of maternal microbiome composition, functional pathways, and mechanisms linked to pregnancy physiology, emphasizing therapeutic interventions such as dietary modulation, probiotics, prebiotics, and microbiota-targeted therapies. By integrating recent evidence from 2023–2025, we highlight the translational potential of microbiome science in optimizing reproductive medicine and maternal-fetal health.
Keywords: infertility, preterm birth, preeclampsia, gestational diabetes, mellitus (GDM), and altered neonatal immune responses